PENERAPAN METODE PEMBELAJARAN AKTIF GROUP RESUME UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN FIQIH KELAS XI IPA DI MA BAHRUL ULUM AIR EMAS KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Fauziah Ramadhani; Andrizal Andrizal; Alhairi Alhairi (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2023)
The learning outcomes of class XI IPA students in Fikih subjects are still relatively low, as evidenced by the existence of student grades under KKM, it takes learning methods that can improve learning outcomes. One of them is the Active Group Resume learning method.Active Group Resume learning methods usually explain the things that individuals have achieved. Group Resume is an interesting way to help students to get to know each other or do some kind of team building whose members already know each other.The purpose of this study is to find out how to apply active group resume learning methods to improve student learning outcomes in fiqh subjects of class XI IPA students at MA Bahrul Ulum Air Emas. The type of research used is Class Action Research (PTK). The study was conducted in three cycles. The subject of this study is the class XI IPA students at MA Bahrul Ulum Air Ema which amounts to 24 students. Data collection techniques used are observation, interviews, tests, and documentation.The results showed that learning using active Group Resume learning methods can improve student learning outcomes, this is evident from the observations obtained in each cycle, starting from Pre-Cycle 37,5%, Cycle I percentage 45,83%, Cycle II percentage 83,33%, and Cycle III percentage 95,83%. Then it can be concluded that, the application of active learning methods Group Resume can improve the learning outcomes of students of class XI IPA MA Bahrul Ulum Air Emas Singingi District Singingi Kuantan Singingi Regency " can improve student learning outcomes.